Leveraging the Quadruple Helix for Sustainable Change in Higher Education - Fitriyah, Shafa Maliya; Hadi, Saiful; Elmhemit, Hüseyin (JURNAL AL-TANZIM, 2025)
This study aims to analyze the role of the Quadrupel Helix model in strengthening the quality of Islamic higher education. The type of research used is qualitative research with a case study approach. Data collection techniques used include interviews, observations, and documentation. The data analysis process is carried out through three stages, namely data reduction, data presentation, and data verification, with an inductive, deductive, and comparative approach. The results of the study indicate that the application of the Quadrupel Helix model in the transformation of the State Islamic Institute (IAIN) into the State Islamic University (UIN) can strengthen the transition process through the synergy of four leading actors. First, government actors play a role in making regulations that facilitate changes in higher education levels. Second, industry actors function to establish cooperation in academic development. Third, academic actors are responsible for managing quality education services. Finally, community actors play a role as active supporters in educational activities. This study provides important implications for the development of Islamic higher education through the application of the Quadrupel Helix model as a strategic foundation for improving academic quality, expanding networks, and creating synergy between government, industry, academics, and society.